Edukasi Tentang Vaksin Covid-19 Pada Masyarakat Desa Buata, Bone Bolango, Provinsi Gorontalo - Teti Sutriyati Tuloli; Robert Tungadi; Ariani Hutuba; Zulfiayu Sapiun (State University of Gorontalo, 2022)
The World Health Organization (WHO) has declared COVID-19 as a Global Pandemic so must be handled in accordance with the legislation. Vaccination is the most effective and efficient public health effort in preventing some dangerous infectious diseases. Even though, it is undeniable that there are still many community groups who refuse vaccination due to a lack of public knowledge regarding the Covid-19 vaccine. This community service Program aims to increase public knowledge about Covid-19 through education with leaflets and and direct socialization to the Buata village community, Botupinge District, Bone Bolango Regency. The results of the Service Implementation show that the Buata village community is very interested in the information conveyed about Covid-19. This is indicated by the presence of various questions about what is the definition of a vaccine, what are the types of Covid-19 vaccines, and what are the side effects of the Covid-19 vaccine. This question has been answered properly and clearly so that the community feels satisfied and very enthusiastic during the implementation of community service programme.